Aggressiveness index of apis mellifera (hymenoptera: aapidae) (2004)
An index measuring the aggressiveness among ten colonies of Apis mellifera was elaborated based on the third generation synthetic indices by Charum et al. (1999). The index values are subject to a fixed parameter used as the beginning or standard value, and correspond to the aggressive features of some Africans colonies studied by Rothenbuler et al. (1968). In the ten colonies the index values are notably smaller than those of African colonies and are biased to the lowest values. This indicates, that neither of the colonies presents an extreme aggressive behavior and it is possible that they have not Africans genotypes. These results are an indirect proof of the index. Nevertheless, it could be improved by the introduction of other factors such as, climate and colony management.